Effects of Food and Temperature on Drosophila melanogaster Reproductive Dormancy as Revealed by Quantification of a GFP-Tagged Yolk Protein in the Ovary - Hara, Yusuke; Yamamoto, Daisuke (Frontiers in Physiology, 2022)
When exposed to harsh environmental conditions such as food scarcity and/or low temperature, D. melanogaster females enter reproductive dormancy, a metabolic state that enhances stress resistance for survival at the expense of reproduction. Although the absence of egg chambers carrying yolk from the ovary has been used to define reproductive dormancy in this species, this definition is susceptible to false judgements of dormancy events: e.g., a trace amount of yolk could escape visual detection; a fly is judged to be in the non-dormancy state if it has a single yolk-containing egg chamber even when other egg chambers are devoid of yolk. In this study, we propose an alternative method for describing the maturation state of oocytes, in which the amount of yolk in the entire ovary is quantified by the fluorescence intensity derived from GFP, which is expressed as a fusion with the major yolk protein Yp1. We show that yolk deposition increases with temperature with a sigmoidal function, and the quality of food substantially alters the maximum accumulation of yolk attainable at a given temperature. The Yp1::GFP reporter will serve as a reliable tool for quantifying the amount of yolk and provides a new means for defining the dormancy state in D. melanogaster.